AGN with extreme X-ray amplitude variations - Gallo L.C.; Leighly K.M.; Komossa S.; Grupe D. (EPJ Web of Conferences, 2012)
We present active galactic nuclei (AGNs) that have shown extreme amplitude variability in X-rays. These AGN appear as bright for long periods, but then suddenly become extremely X-ray weak sources. Most likely this behavior is due to strong absorption along the line of sight or by relativistically blurred reflection. Two extreme examples are the Narrow Line Seyfert 1 (NLS1) galaxies WPVS 007 and Mkn 335. WPVS 007 is a peculiar AGN because it combines the properties of a normal NLS1 with those of a broad-absorption line (BAL) quasar, which typically only appear in high-luminousity, high black hole mass systems. Mkn 335 has appeared an an X-ray bright AGN for most of the past few decades, but was caught by Swift in a deep X-ray flux minimum state in 2007, and has remained in that state for most of the time since. One potential explanation for this low state is absorption. Several Other AGN have been in deep minimum X-ray flux states, including PG 0844+349 and 1H 0707–495, for which the dramatic drops in X-ray flux have been explained by blurred X-ray reflection.